The Correlation Between the Level of Stress and The Independence Of The Elderly In Fulfilling The Activity Of Daily Living At The Posyandu, Tunggulwulung District - Risma Dwi Sholikhatun; wiwik Agustina; Rahmawati Maulidia (Jurnal Keperawatan Malang, 2022)
ABSTRACT Background: Stress is the body's response to an unpleasant environment where a person sees it as a problem or a burden and the inability to meet its demands. One of the responses that occur due to stress is an emotional response, the symptoms can be anxiety, mood disorders and a decrease in productivity, one of which can occur in daily activities. Purpose: To determine the correlation between stress levels and the independence of the elderly in fulfilling the Activity Of Daily Living at the posyandu for the elderly at the district of Tunggulwulung. Methods: Correlational design with a cross sectional approach to determine the correlation between two variables, the independent variable is the level of stress and the dependent variable is the independence of the elderly in fulfilling the Activity Of Daily Living by observing. The sample in this study amounted to 36 respondents. Sampling using purposive sampling technique. Result: The results of statistical test obtained p value = 0,000 the value p is smaller than (0,05) Conclusion: There were a significant relationship between the level of stress and the independence of the elderly in fulfilling the Activity Of Daily Living at the Posyandu, Tunggulwulung District. Key words: Activity Of Daily Living; Elderly; The level of Stres.